A Computational Analysis on the Effect of deleterious nsSNPs in GALE Qene - RAMAVARTHENI KANTHAPPAN; RAO SETHUMADHAVAN (International Journal of Pharma and Bio Sciences, 2010)
Single nucleotide polymorphisms (SNPs), present in the protein encoding regions of the genome can have a profound influence on the structure and function of a protein. In this work, we have analyzed the mutations that can alter the function of the GALE gene through computational methods with the help of tools like SIFT, PolyPhen and UTRscan. We observed that about 61.54% of the total nsSNPs were damaged by the SIFT, 53.85% by the PolyPhen and 38.46% by both the servers. Then we proposed a modeled structure for the mutant proteins (G227A, G235A and N268K) and compared it with the native protein. Also the RMSD values between the native and mutant (G227, G235A and N268K) type proteins were 1.52Å, 1.67Å and 1.74Å. We suggest that our results will provide useful information in selecting the target SNPs that are likely to have functional impact on the GALE gene and contribute to an individual’s susceptibility to the disease.